Laboratory measurements of the optical properties of sea salt aerosol - Irshad, R; Grainger, D; Peters, D; McPheat, R; Smith, K; Thomas, G (Copernicus Publications, 2009)
The extinction spectra of laboratory generated sea salt aerosols have been measured from 1μm to 20μm using a Bruker 66v/S FTIR spectrometer. Concomitant measurements include temperature, pressure, relative humidity and the aerosol size distribution. The refractive indices of the sea salt aerosol have been determined using a simple harmonic oscillator band model (Thomas et al., 2004) for aerosol with relative humidities at eight different values between 0.4% to 86%. The resulting refractive index spectra show significant discrepancies when compared to existing sea salt refractive indices calculated using volume mixing rules (Shettle and Fenn, 1979). Specifically, an additional band is found in the refractive indices of dry sea salt aerosol and the new data shows increased values of refractive index at almost all wavelengths. This implies that the volume mixing rules, currently used to calculate the refractive indices of wet sea salt aerosols, are inadequate. Furthermore, the existing data for the real and imaginary parts of the refractive indices of dry sea salt aerosol are found not to display the Kramers-Kronig relationship. This implies that the original data used for the volume mixing calculations is also inaccurate.